Comparing cartel behavior: A simulation analysis with the System of Cartel Markers (SCM) - Jan Hendrik Preißler-Jebe; Korbinian von Blanckenburg; Alexander Geist (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
This work simulates the behavior of a price, quota and regional cartel in terms of indicators such as price, capacity and rate of return. As a first step the specific behavior patterns of each cartel are indicated in a graphical analysis before a comparison to a competitive benchmark has been implemented. In a second step simulation data has been applied to the System of Cartel Markers (SCM) invented by Blanckenburg and Geist. The SCM uses empirical correlation and stationarity of indicators to provide empirical evidence for cartel behavior. For the simulated cartel data the SCM delivered consistent results which underline its functionality for simulation purposes.
Keywords: 330